Mycobacterium leprae Survival Inside Acanthamoeba sp. Isolated from Water Source in Leprosy Endemic Area, Indonesia: Mycobacterium leprae Survival Inside Acanthamoeba sp. - Wahyuni, Ratna; Astari, Linda; Iswahyudi, Iswahyudi; Paling, Sepling; Adriaty, Dinar; Kurniawati, Siti; Aulia, Syifa; Rahmatari, Bandaru; Prakoeswa, Cita Rosita; Agusni, Indropo; Izumi, Shinzo (Journal of Tropical Life Science, 2024)
Mycobacterium leprae is an acid-fast bacterium that causes leprosy diseases, which remains a problem worldwide. Even though leprosy prevalence in the world has decreased significantly, many endemic pocket areas continue reporting new cases and harbor M. leprae in the environment, including water and soil. The presence of obligate intracellular bacteria-M. leprae in the environment raises a question on how it survives. Free-living amoeba has been proposed as its reservoir host in the environment. The study was conducted to give evidence that M. leprae can survive inside free-living amoeba isolated from water sources of leprosy endemic areas. M. leprae from leprosy patients was cultured together with Acanthamoeba sp. isolated from the water source of the leprosy endemic area. Viability and duplication of M. leprae inside amoeba then observed at day 14 and 28 using reverse transcriptase PCR and qPCR. The results showed that M. leprae survived inside the amoeba until day 28, but no bacterial replication was observed. The study reveals in vitro evidence of viable M. leprae inside free-living amoeba of leprosy endemic area environment.